TET2 Protects against oxLDL-Induced HUVEC Dysfunction by Upregulating the CSE/H2S System - Peng, Juan; Tang, Zhi-Han; Ren, Zhong; He, Bei; Zeng, Yun; Liu, Lu-Shan; Wang, Zuo; Wei, Dang-Heng; Zheng, Xi-Long; Jiang, Zhi-Sheng (Frontiers in Pharmacology, 2017)
Ten-eleven translocation-2 (TET2) protein is a DNA demethylase that regulates gene expression through DNA demethylation and also plays important roles in various diseases including atherosclerosis. Endothelial dysfunction represents an early key event in atherosclerotic disease. The cystathionine--lyase (CSE)/hydrogen sulfide (H2S) is a key endogenous system with protective effects on endothelial functions. In this study, we examined how TET2 regulates oxidized low-density lipoprotein (oxLDL)-induced dysfunction of human umbilical vein endothelial cells (HUVECs) and determined the role of the CSE/H2S system. Treatment with oxLDL resulted in downregulation of both TET2 expression and CSE/H2S system in HUVECs. TET2 was found to have protective effects on oxLDL-induced HUVEC dysfunction, which was confirmed with TET2 overexpression plasmid or TET2 shRNA plasmid. Moreover, TET2 was found to upregulate the CSE/H2S system and inhibit NF-κB activation, leading to decreased expression of ICAM-1 and VCAM-1 and attenuated adhesion of THP-1 cells to oxLDL-activated HUVECs. The protective effect of TET2 was reduced by treatment with CSE siRNA. Further studies revealed that CSE promoter region contains a well-defined CpG island. We also showed that TET2 enhanced 5-hydroxymethylcytosine (5hmC) level and promoted DNA demethylation of CSE gene promoter, leading to an increase in CSE expression. In conclusion, TET2 has protective effects on oxLDL-induced HUVEC dysfunction, likely through upregulating the CSE/H2S system by DNA demethylation of CSE gene promoter. TET2 may become a novel therapeutic target for endothelial dysfunction-associated vascular diseases.